PENINGKATAN HASIL BELAJAR SISWA MEMBACA NOTASI BALOK MENGGUNAKAN ALAT MUSIK DI SMPN 4 PARIAMAN - Tri Chintia Maressa; Jagar Lumban Toruan; Yuliasma Yuliasma (SENDRATASIK UNP, 2013)
Abstract This research aimed at describing the improvement of students learning outcomes in reading musical notations in songs by using pianika and rekorder at the class of VII.7 of SMP Negeri 4 Pariaman. The design of this research was class action research. The objects of this research were 30 students of class VII.7 SMP Negeri 4 Pariaman. From the data analysis, it was found that there was an improvement on students learning outcomes. It was seen from their learning outcomes average scores. In the first cycle, the average score was 47.3. In the second cycle, it increased into 70.6 while the intended average score was only 70. From the findings, it was concluded that the use of pianika dan rekorder improved students learning outcomes in reading musical notations in songs. Kata Kunci: Hasil Belajar, Membaca Notasi Balok, Alat Musik,  Pianika dan Rekorder.